2022
DOI: 10.1021/acs.jpca.2c04408
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Kinetics of the Reaction between CH2OO and H2O2 in the Atmosphere

Abstract: Criegee intermediates (CIs) are generated from the ozonolysis of unsaturated hydrocarbons in the atmosphere. They have an important role in determining the implications of atmospheric bimolecular reactions with other atmospheric species. The reaction between CH2OO and H2O2 plays a crucial role in understanding how CIs impact the HO x budget in the atmosphere. The reaction mechanism and kinetics are critical to atmospheric modeling, which is a prominent challenge in present-day climate change modeling. This is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 115 publications
0
5
0
Order By: Relevance
“…This also shows that DF-CCSD(T)-F12b/jun-cc-pVDZ can obtain quantitative geometrical parameters and zero-point vibrational energies, which was found in our previous investigations. 39,68,69 Therefore, DF-CCSD(T)-F12b/jun-cc-pVDZ is used to investigate the anti-CH 3 CHOO/syn-CH 3 CHOO + CH 3 CN reactions.…”
Section: The Electronic Structure Of the Ch 2 Oo + Ch 3 Cn Reactionmentioning
confidence: 99%
“…This also shows that DF-CCSD(T)-F12b/jun-cc-pVDZ can obtain quantitative geometrical parameters and zero-point vibrational energies, which was found in our previous investigations. 39,68,69 Therefore, DF-CCSD(T)-F12b/jun-cc-pVDZ is used to investigate the anti-CH 3 CHOO/syn-CH 3 CHOO + CH 3 CN reactions.…”
Section: The Electronic Structure Of the Ch 2 Oo + Ch 3 Cn Reactionmentioning
confidence: 99%
“…Previous investigations have shown that W3X-L//CCSD­(T)-F12a/cc-pVTZ-F12 , method can obtain quantitative enthalpies of activation at 0 K for the reactions involving Criegee intermediates. Therefore, W3X-L//CCSD­(T)-F12a/cc-pVTZ-F12 was used to calculate reaction between the simplest Criegee intermediate (CH 2 OO) and hypochlorous acid (HOCl). Specifically, CCSD­(T)-F12a/cc-pVTZ-F12 , was used to do geometrical optimizations and frequency calculations.…”
Section: Computational Methods and Strategiesmentioning
confidence: 99%
“…Among the important kinetic pathways followed by Criegee intermediates under thermal conditions are: conformational dynamics (involving rotation about one or more carbon–carbon or carbon–oxygen bond within the molecule), hydrogen transfer reactions (which can lead to the formation of OH radicals via hydroperoxide formation), ring-closing reactions (leading to the formation of dioxirane structures), and alternative ring-closing mechanisms (leading to formation of dioxole structures). , Many of the dioxole and dioxirane structures are believed to undergo further unimolecular decay. With respect to the ozonolysis of isoprene, the majority of the experimental and theoretical studies have focused on the properties and reactivity of MVK , , and formaldehyde oxides, , with MACR oxide being relatively less studied. , , At the same time, it is clear that MACR oxide can play an important role in the ozone-derived chemistry of isoprene: as described by others, and discussed below, anti-MACR oxide is unusually long-lived (τ ≈ 0.10 s at 298 K) with respect to unimolecular decay, ,, making this Criegee intermediate a potentially potent contributor to bimolecular chemistry in the atmosphere.…”
Section: Introductionmentioning
confidence: 99%